Research on the Improvement of Wear Resistance of Si3N4 Substrate by Magnetron Sputtering Deposition of TiN Thin Films with Different Film Structures - WANG He, CHEN Sibo, YAN Guangyu, WU Yuhou, CHU Jianxiang, DAI Guangyuan (Cailiao Baohu)
In order to solve the problem that the surface of silicon nitride ceramic bearings is susceptible to wear under extreme operating conditions，gradient，multilayer and monolayer TiN films were prepared on silicon nitride substrates using magnetron sputtering.Three nitrogen supply modes were implemented: a gradual increase starting at 15 mL/min with 0.8 mL/min increments every 5 min，an alternating on-off switching between 0 and 30 mL/min，and a constant 30 mL/min flow.The influence of film structure on surface morphology，cross-sectional morphology and microstructure was investigated using X-ray diffractometer (XRD) and scanning electron microscopy (SEM)，while the filmsubstrate adhesion and tribological properties were evaluated through scratch and friction-wear tests.Results showed that under identical testing conditions，the gradient TiN film exhibited the highest film-substrate adhesion strength (LC2 ＝19.12 N)，representing an approximately 30%improvement compared to the monolayer TiN film.Compared to silicon nitride’s friction coefficient (0.78) and wear rate [1.51×10－5 mm3/(m·N)]，both the friction coefficients and wear rates of TiN films with different film structures significantly decreased.Among them，the gradient TiN film exhibited the lowest friction coefficient (0.10) and the lowest wear rate [3.33×10－6 mm3/(m·N)].Different film structure designs significantly influenced the microstructure，film-substrate adhesion and tribological properties of TiN coatings.The film with the best tribological properties was a gradient TiN film structure.